Avaliação de potenciais antígenos vacinais e geração de aptâmeros por cell-SELEX em Erysipelothrix rhusiopathiae - Monteiro, Vinícius Marquioni (Universidade Federal de São Carlos, 2018)
Erysipelothrix rhusiopathiae is a Gram-positive bacterium that causes the disease known as swine erysipelas. Available veterinary vaccines against the disease have several limitations and methods for detecting the bacterium are time consuming and expensive. In a previous work, candidate antigenic proteins were identified in the supernatant of E. rhusiopathiae cultures by an immunoproteomic analysis. In the present work, some of the identified proteins were cloned and expressed to assess their antigenicity and protective ability against E. rhusiopathiae. In parallel, by the cell-SELEX technique, aptamers capable of binding to E. rhusiopathiae cells were selected, which could be incorporated into bacterial detection systems. Eleven proteins were selected for cloning and recombinant expression. The ORFs of these proteins were amplified by PCR, cloned into a propagation vector (pJET1.2/blunt) and sub-cloned into an expression vector (pET28a). Nine proteins were expressed in E. coli BL21(DE3), five of which could be sufficiently purified by chromatography for an antibody titration using the serum of pigs immunized against swine erysipelas, of which three were confirmed as antigenic. Two antigenic proteins obtained in sufficient yield and purity were subjected to a mouse immunization assay and showed a possible protective effect when the animals were challenged with 1,000 E. rhusiopathiae cells. However, with a challenge of 10,000 cells, almost all immunized animals died, as well as those vaccinated with a commercial vaccine. Selection of aptamers by cell-SELEX (SELEX performed with whole cells) was carried out in seven cycles, with increasing stringency, using a library with conserved 5' and 3' regions and a central region with 40 random nucleotides. After cloning, the aptamers were reamplified with an F primer labeled with the fluorophore 6-FAM for characterization of their binding to cells by flow cytometry. Twenty E. coli clones containing cloned aptamers were randomly selected for sequencing. Only six distinct sequences were obtained which were grouped into three families, with no more than one base differing among sequences of the same family, suggesting that cell-SELEX was efficient in enriching the initial library in sequences capable of binding to E. rhusiopathiae. In the future, the immunization assay with the two selected antigenic proteins may be repeated with an amount of bacteria intermediate to those tested, allowing a better evaluation of their protective ability against E. rhusiopathiae. As for the aptamers, now with known sequences, it will be possible to properly characterize them. This work suggested two E. rhusiopathiae proteins as promising vaccine antigens, as well as aptamers that are possibly specific for the pathogen which could later be incorporated into bacterial detection systems.
Evaluation of potential vaccine antigens and generation of aptamers in Erysipelothrix rhusiopathiae
Keywords: Erysipelothrix rhusiopathiae; Erisipela suína; Vacinas; Antígenos; Aptâmeros; cell-SELEX; Proteínas recombinantes; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA APLICADA